Global Governance of Biogenic Threats - M. M. Lebedeva; D. A. Kuznetsov (Vestnik MGIMO-Universiteta)
The SARS-CoV-2 virus, which caused a pandemic in 2020, has posed not only a medical, economic and social threat, but also a challenge to international security and international cooperation. It is now becoming obvious that the problem of the current pandemic cannot be reduced to individual states and regions and has the potential to influence the entire political organization of the modern world. Analyzing the role of the COVID-19 pandemic in world politics, the authors rely on the concept of transformations in the system of the world political organization, as well as the concept of global governance and megatrends of world politics, the key of which is globalization. The authors of the article consider the experience of individual global and regional associations, which are considered to be the elements of global governance, whose functions, among the other, include responding to challenges of a biogenic nature, identifying several important trends, among which are the intensification of previously emerging trends, the strengthening of isolationism, the growing political fragmentation of the world, destructive influence of “coronacrisis” on globalization, but with parallel sectoral polarization in global economy, a new balancing between cooperation and competition in international relations. At the same time, it is argued that there is no alternative to international cooperation in solving problems of a global nature, which can hardly indicate the end of globalization and the triumph of disintegration and de-democratization. The authors argue about the heightened need to reform global governance, since the efforts of individual international associations cannot lead to solving global challenges, and the national-centrist approach to solving global problems proves its inefficiency and irresponsibility. As a result, we are talking about the lack of alternative to the idea of forming a system of global governance, which should be based on cooperation and interaction of states, international organizations and institutions, as well as business structures and academic communities, in other words, rely on multilateral and multilevel approach. The authors are convinced of the need to develop a project of an “ideal future” taking into account the identified trends in the transformation of the political organization of the world and the effects of megatrends, which implies the further development of scientific research and discussions, as well as a series of international negotiating forums on the future structure of the world and the corresponding pattern of global governance.